(untitled) (Research, Society and Development, 2021)
The objective of this study was to report the occurrence of Dioctophyme renale in the left kidney of feline along with the presence, and the occurrence of left perirenal fibrosarcoma. It was attended in hospital veterinary of the UFPel at a 10-year-old cat complaining of abdominal pain and prostration was treated. Imaging studies suggested neoplasms in the left perirenal region. The animal underwent laparotomy where intense adhesion of a tumor mass to the kidney was observed, which led to nephrectomy of the left kidney. Tumor mass and left kidney were referred for histopathological study. On macroscopic examination, the affected kidney had parenchymal atrophy and the organ capsule was thickened and cystic aspect was seen with a yellowish liquid content and structures similar to a degenerate Dioctophyme renale. The tumor mass was whitish, firm and well vascularized. Histologically, pleomorphic, sarcomatous neoplastic cells and fibrous connective tissue stroma were observed that could be arranged in bundles or nests. The Masson’s Trichrome staing showed collagen fibers and fibrous connective tissue stroma allowing the diagnosis of fibrosarcoma. In this report, three unusual facts were discussed: a) occurrence of Dioctophyme renale in felines b) left kidney involvement. c) perirenal fibrosarcoma with the suggestion of some involvement with Dioctophyme renale parasitism.